Subclinical cardiac structural and electrical abnormalities in fibromyalgia syndrome - Aksu, Ekrem; Berk, Ejder; Sökmen, Abdullah; Sökmen, Gülizar; Çelik, Enes (Turkish journal of medical sciences, 2020)
In the literature, there is a paucity of data about the effects of fibromyalgia syndrome (FMS) on myocardial function and electrophysiological properties of atrium and ventricles. In this study, we investigated cardiac functions and noninvasive predictors of arrhythmias in patients with FMS. The study included 43 female patients diagnosed with FMS and 30 age- and sex-matched healthy subjects. The presence of fragmented QRS (fQRS) morphology, P dispersion, QT dispersion, inter- and intraatrial electromechanical delay was evaluated in the groups with 12-lead ECG and standard and tissue Doppler echocardiography. Among electrocardiographic parameters, P dispersion, QT dispersion, and the ratio of presence of fQRS morphology were found to be significantly higher in the study group as compared to the control group. In lateral and septal, the ratio of the early transmitral flow velocity to the early diastolic tissue velocity (E/Em) was significantly higher in the study group. Additionally, intra- and interatrial electromechanical delay was found significantly prolonged in the study group. FMS is found to be associated with significant cardiac electrical alterations that may indicate the increased risk of atrial and ventricular arrhythmias in this group of patients.